India: Media Labs Asia/Kanpur-Lucknow Lab (KKL) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Media Labs Asia/Kanpur-Lucknow Lab (KKL) have developed the ´infothela´, a mobile, battery-powered unit mounted on a tricycle, equipped with a telephone, fax machine, and a computer to access the Internet, to take the benefits of ICTs to peopl